The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1155/2014/371475
|View full text |Cite
|
Sign up to set email alerts
|

Acupoint‐Specific, Frequency‐Dependent, and Improved Insulin Sensitivity Hypoglycemic Effect of Electroacupuncture Applied to Drug‐Combined Therapy Studied by a Randomized Control Clinical Trial

Abstract: The application of electroacupuncture (EA) to specific acupoints can induce a hypoglycemic effect in streptozotocin-induced rats, normal rats, and rats with steroid-induced insulin resistance. EA combined with the oral insulin sensitizer rosiglitazone improved insulin sensitivity in rats and humans with type II diabetes mellitus (DM). There are different hypoglycemic mechanisms between Zhongwan and Zusanli acupoints by EA stimulation. On low-frequency (2 Hz) stimulation at bilateral Zusanli acupoints, serotoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…A recent meta-analysis reported that acupuncture, in particular auricular acupuncture and electro-acupuncture, was more efficacious than sham acupuncture for reducing BMI (MD − 0.47 kg/m 2 ) as well as body fat mass (MD − 0.66 kg), waist circumference (MD − 2.02 cm) and hip circumference (MD − 2.74 cm) but not for reducing body weight overall [20]. Mechanistic studies have suggested multiple responses to acupuncture including appetite suppression [21,22], modulation of leptin and ghrelin [23][24][25] and improved insulin sensitivity [26][27][28][29][30][31]. Further, acupuncture may alleviate co-morbid anxiety symptoms in people with obesity [23,32,33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis reported that acupuncture, in particular auricular acupuncture and electro-acupuncture, was more efficacious than sham acupuncture for reducing BMI (MD − 0.47 kg/m 2 ) as well as body fat mass (MD − 0.66 kg), waist circumference (MD − 2.02 cm) and hip circumference (MD − 2.74 cm) but not for reducing body weight overall [20]. Mechanistic studies have suggested multiple responses to acupuncture including appetite suppression [21,22], modulation of leptin and ghrelin [23][24][25] and improved insulin sensitivity [26][27][28][29][30][31]. Further, acupuncture may alleviate co-morbid anxiety symptoms in people with obesity [23,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity levels were calculated according to the number of 20-min sessions of less vigorous exercise or more vigorous exercise a week, given a weighting and described in terms of MET (metabolic cost) minutes where MET minutes less than 80 were coded as no physical activity, 80 to 400 as low, 400 to 560 as moderate and more than 560 as high. A value of 4 METs was given to moderate physical activity and 7.5 to vigorous physical activity [26].…”
Section: Lifestyle Habitsmentioning
confidence: 99%
“…In non-PCOS populations, acupuncture, in particular auricular acupuncture and electro-acupuncture, is more efficacious than sham for reducing body mass index (BMI) (mean difference [MD] − 0.47 kg/m 2 ) as well as body fat mass (MD − 0.66 kg), waist circumference (MD − 2.02 cm) and hip circumference (MD − 2.74 cm) [8]. These effects are mediated through multiple responses including appetite suppression [9,10], modulation of leptin and ghrelin [11][12][13], and improved insulin sensitivity [14][15][16][17][18][19]. Further, acupuncture may alleviate comorbid anxiety symptoms in people with obesity [11,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Each acupoint has its different therapeutic action. The acupoints can be stimulated either manually using needle or electrically 8 . Acupuncture therapy in diabetes acts on the receptors of pancreas beta cells to increase the insulin secretion, promotes glucose metabolism and reduce the blood sugar level 9 .…”
Section: Introductionmentioning
confidence: 99%